COST AND TIME ANALYSIS USING EARNED VALUE METHOD BUILDING CONSTRUCTION OF DISTANCE LEARNING PROGRAM UNITS OF SURABAYA OPEN UNIVERSITY PHASE II - Asmoro, Mochamad Ranoe; Witjaksana, Budi; Tjendani, Hanie Teki (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2024)
Project delays often serve as a catalyst for conflicts and disagreements between project owners and contractors, leading to significant financial implications. Such delays result in costly consequences for both parties involved. Contractors face the imposition of penalty fines as stipulated in the contractual agreement, alongside incurring overhead costs during the prolonged project duration. Conversely, owners experience a direct impact on their revenue streams due to delays in the operationalization of the facility. In the context of the construction of the Surabaya Open University Distance Learning Program Unit building phase II, the examination of cost and time performance becomes imperative. Employing the earned value method offers a comprehensive approach to project performance evaluation, involving a meticulous comparison of actual expenses and timelines with the initially anticipated costs. This analytical approach aids in understanding the project's progress and identifying areas where adjustments may be necessary to mitigate potential delays. The Earned Value Method (EVM) analysis of the Surabaya Open University Distance Learning Program Unit building phase II reveals a projected total cost of IDR 73,908,443,223.09 by the time the project reaches completion. This estimation provides stakeholders with valuable insights into the financial commitment required for the successful conclusion of the project. Additionally, the anticipated timeline for completion is estimated at 53 weeks, serving as a crucial parameter for project planning and management.